2016
DOI: 10.1002/psp4.12092
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Based Assessment of Alternative Study Designs in Pediatric Trials. Part II: Bayesian Approaches

Abstract: This study presents a pharmacokinetic‐pharmacodynamic based clinical trial simulation framework for evaluating the performance of a fixed‐sample Bayesian design (BD) and two alternative Bayesian sequential designs (BSDs) (i.e., a non‐hierarchical (NON‐H) and a semi‐hierarchical (SEMI‐H) one). Prior information was elicited from adult trials and weighted based on the expected similarity of response to treatment between the pediatric and adult populations. Study designs were evaluated in terms of: type I and II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The merged distribution is called the posterior distribution and is used for data analysis. 36,37 In order to apply this approach, one has to assume that the historical data used to create the assumed distribution is applicable to the study population. One way of applying Bayesian statistics to pediatric trials is using data from uncontrolled pediatric studies or from adult studies as historical data.…”
Section: Discussionmentioning
confidence: 99%
“…The merged distribution is called the posterior distribution and is used for data analysis. 36,37 In order to apply this approach, one has to assume that the historical data used to create the assumed distribution is applicable to the study population. One way of applying Bayesian statistics to pediatric trials is using data from uncontrolled pediatric studies or from adult studies as historical data.…”
Section: Discussionmentioning
confidence: 99%
“…I-ACT and PTN share a goal of providing expert advice on CT design and conduct for drugs and medical devices in children. The Global Research in Pediatrics (GRiP) Network of Excellence, funded by the European Union has developed guidance and research tools for pediatric studies ( 24 , 25 , 26 , 27 , 28 ) that can be found in their publication repository ( http://www.grip-network.org/index.php/cms/en/publications ). The advantages of these international partnerships include harmonization, development of best research practice, and a global union of expertise and experience in pediatric clinical research.…”
Section: Current Regulatory Guidancementioning
confidence: 99%
“…Some investigators have found that many factors such as protocol approval by sites, limited knowledge of methodology, lack of in-depth understanding of child physiology, psychology, the social embedding of children may hinder the use of innovative methods, 24 but experience is growing. [25][26][27][28] Networks can contribute to the design of trials in a number of ways, including registries 29 and modelling. 30,31 Trial design depends on understanding the clinical context of the trial: "trial designs, no matter how novel, will only be as good as the knowledge that underlies them."…”
Section: Optimal Design Of Studiesmentioning
confidence: 99%